2004
DOI: 10.1111/j.1464-5491.2004.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Structured treatment and teaching of patients with Type 2 diabetes mellitus and impaired cognitive function—the DICOF trial

Abstract: Elderly patients with impaired cognitive function should take part in specialized structured TTP. This leads to both better satisfaction with the education programme and an improved ability for diabetes self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
1
26
0
4
Order By: Relevance
“…In the study by Peel et al [26], patients with type 2 diabetes mellitus often tend not to respond adequately to their measured self-monitoring results, in part because of lack of education about the appropriate response to readings. The improvement in patients' self-management skills by delivering a structured DTTP has already been studied [11] and the findings of our study support that DTTP has also an impact on diabetes-related QoL. In our study, self-management skills showed a slight deterioration at the follow-up visit, but selfmanagement skills were only assessed immediately and 6 months after participation in the DTTP.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the study by Peel et al [26], patients with type 2 diabetes mellitus often tend not to respond adequately to their measured self-monitoring results, in part because of lack of education about the appropriate response to readings. The improvement in patients' self-management skills by delivering a structured DTTP has already been studied [11] and the findings of our study support that DTTP has also an impact on diabetes-related QoL. In our study, self-management skills showed a slight deterioration at the follow-up visit, but selfmanagement skills were only assessed immediately and 6 months after participation in the DTTP.…”
Section: Discussionsupporting
confidence: 83%
“…The patients participating in the present study started on a high mean HbA1c level and were treated according to the guidelines of the German Diabetes Association, which recommend the start of insulin therapy in older patients with insufficient metabolic control with oral antidiabetic drug therapy to achieve a target HbA1c of at least 8% [4]. The effect of DTTP on metabolic control has already been proven in several studies [10][11][12][13]22]. The present study shows that HbA1c levels are associated with a higher diabetes-related QoL-score at the second examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In aller Regel sind konventionelle Schulungsprogramme für geriatrische Patienten zu komplex [4,17,19]. Dagegen konnte die spezielle "strukturierte geriatrische Schulung" (SGS) für ältere bzw.…”
Section: Immer Mehr Immer äLtere Menschen -Auch Mit Diabetesunclassified